2023
DOI: 10.3389/fpls.2023.1088537
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and metabolomic analyses reveal the potential mechanism of waterlogging resistance in cotton (Gossypium hirsutum L.)

Abstract: IntroductionCotton (Gossypium hirsutum L.) is susceptible to long-term waterlogging stress; however, genomic information of cotton response mechanisms toward long days of waterlogging is quite elusive.MethodsHere, we combined the transcriptome and metabolome expression level changes in cotton roots after 10 and 20 days of waterlogging stress treatment pertaining to potential resistance mechanisms in two cotton genotypes.Results and discussionNumerous adventitious roots and hypertrophic lenticels were induced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…In the context of waterlogging stress, different plant varieties can exhibit significant impacts on metabolic pathways and gene transcription levels. For instance, flood-tolerant onions demonstrated a higher prevalence of downregulated genes [ 37 ], while cotton displayed a robust response involving antioxidant enzyme genes and transcription factor genes after 20 days of waterlogging [ 14 ]. Similarly, waterlogging stress induced notable changes in gene expression and metabolites in CMD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of waterlogging stress, different plant varieties can exhibit significant impacts on metabolic pathways and gene transcription levels. For instance, flood-tolerant onions demonstrated a higher prevalence of downregulated genes [ 37 ], while cotton displayed a robust response involving antioxidant enzyme genes and transcription factor genes after 20 days of waterlogging [ 14 ]. Similarly, waterlogging stress induced notable changes in gene expression and metabolites in CMD.…”
Section: Discussionmentioning
confidence: 99%
“…For example, onion ( Allium cepa L.) showed significant changes in the phenylalanine metabolic pathway, pathogenesis-related proteins, and energy production after 72 h of waterlogging treatment [ 37 ]. Cotton ( Gossypium hirsutum L.) showed a significant increase in several metabolites including sinapyl alcohol, adenosine, and galactaric acid after 10–20 days of waterlogging [ 14 ]. The mechanisms by which CMD responds to waterlogging stress are different from the literature, but there are similarities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression levels of three sucrose phosphate synthase genes (ZjSPS1, scaffold1731.36; ZjSPS2, scaffold19851.46; and ZjSS2, scaffold41823.29) were found to be positively correlated with sucrose content in fruits [43]. [44] identified 19 ZjSWEET genes based on gene family analysis and observed that the expression levels of 2 genes (ZjSWEET11, LOC107404505 and ZjSWEET18, LOC107417626) progressively increased during fruit development, peaking at the full red fruit stage. Several other ZjSWEET genes were found to play vital roles in abiotic stress conditions.…”
Section: Sugar and Organic Acid Accumulation And Metabolismmentioning
confidence: 99%
“…In recent years, the advent of next-generation sequencing has revolutionized plant biology research, offering a cost-effective solution, even in non-model systems [17]. Secondgeneration sequencing data correlation analysis, particularly, has successfully unraveled molecular mechanisms governing the formation of multiple crop traits and the synthesis of biological components [18][19][20]. These methodologies have found widespread application in jujube studies.…”
Section: Introductionmentioning
confidence: 99%